Performance Comparison of Different Mutual Funds Schemes in India Through Sharpe Index Model - Bhatt, Mayank V.; Patel, Chetan C. (Indian Journal of Finance, 2008)
Mutual Fund is an investment company that pools money from shareholders and invests in a variety of securities, such as stocks, bonds and short term money market instruments or other securities. In a mutual fund, the fund manager trades the fund's underlying securities, realizing capital gains or loss and collects the dividend or interest income. The investment proceeds are then passed along to the individual investors. The value of a share of the mutual fund, known as the net asset value (NAV), is calculated daily based on the total value of the fund divided by the number of shares purchased by investors.